DMT1 iron uptake in the PNS: bridging the gap between injury and regeneration - Martínez Vivot, Rocío (2015)
Previous work by our group demonstrated the key role of iron in Schwann cell (SC)maturation through an increase in cAMP, PKA activation and CREB phosphorylation. These studies opened the door to further research on a non-transferrin-bound iron uptake, which revealed the presence of DMT1 mRNA all along SC progeny, hinting at a constitutive role of DMT1 in ensuring the provision of iron in the PNS. In light of these previous results,the present work evaluates the participation of DMT1 in the remyelination process following a demyelinating lesion promoted by sciatic nerve crush ?a reversible model of Wallerian degeneration. DMT1 was observed to colocalize with SC marker S100β at all survival times analyzed. In turn, the assessment of DMT1 mRNA expression exhibited an increase 7 days post-injury, while DMT1 protein levels showed an increase 14 days after crush at the lesion site and distal stump; finally, an increase in iron levels became evidentas from 14 days post-injury, in parallel with DMT1 values. To sum up, the present work unveils the role of DMT1 in mediating the neuroregenerative action of iron.